2016
DOI: 10.1039/c6ra13584f
|View full text |Cite
|
Sign up to set email alerts
|

An efficient synthesis of 1,3-dimethyl-5-(2-phenyl-4H-chromen-4-ylidene) pyrimidine-2,4,6(1H,3H,5H)-triones and investigation of their interactions with β-lactoglobiulin

Abstract: An efficient method for synthesis of 1,3-dimethyl-5-(2-phenyl-4H-chromen-4-ylidene)pyrimidine-2,4,6(1H,3H,5H)-triones has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…This molecular detail helps to predict how much they are potential to take part in chemical reaction and to realize their mechanism of interactions. The high potential energy regions are electron poor (blue) and the low potential parts having correspondingly low potential energy (Red) and the neutral region is green [21].…”
Section: Molecular Electrostatic Potential (Mep) Analysismentioning
confidence: 99%
“…This molecular detail helps to predict how much they are potential to take part in chemical reaction and to realize their mechanism of interactions. The high potential energy regions are electron poor (blue) and the low potential parts having correspondingly low potential energy (Red) and the neutral region is green [21].…”
Section: Molecular Electrostatic Potential (Mep) Analysismentioning
confidence: 99%
“…β ‐Lactoglobulin ( β ‐lg), a carrier protein, is one of the main lipocalin proteins of whey. Its binding properties with varieties of organic molecules have been the subject of study on several occasions ,. This aspect encouraged us to explore the binding of the compounds of series 4 , all of which are new, with β ‐lg.…”
Section: Resultsmentioning
confidence: 99%
“…This aspect encouraged us to explore the binding of the compounds of series 4 , all of which are new, with β ‐lg. The presence or absence of interaction was investigated by study of fluorescence spectra resulting from gradual addition of 4 to the protein in 5% aqueous ethanolic phosphate buffer (pH=7.4) ,. It was observed that the fluorescence intensity of β ‐lg at 337 nm decreased in the presence of increasing concentrations of 4 at pH 7.4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This molecular detail helps to predict how much they are potential to take part in chemical reaction and to realise their mechanism of interactions. In addition to this, the surfaces provide the lower limit of the proximity of two molecules which describe the steric feature of the molecule [24]. Therefore, the quantum mechanically calculated properties of an energy minimised molecular geometry help to understand the steric, electronic feature and nature of binding forces of molecules.…”
Section: Molecular Electrostatic Potential (Mep) Analysismentioning
confidence: 99%